Drivers of soil organic carbon from temperate to alpine forests: a model-based analysis of the Swiss forest soil inventory with Yasso20 - C. Guidi; S. Gosheva-Oney; S. Gosheva-Oney; M. Didion; R. Flury; L. Walthert; S. Zimmermann; B. J. Oney; P. A. Niklaus; E. Thürig; T. Viskari; T. Viskari; et al. (Biogeosciences)
Predicting soil organic carbon (SOC) stocks and their dynamics in forest ecosystems is crucial for assessing forest C balance, but the relative importance of key controls – litter inputs, climate, and soil properties – remains uncertain. Here, we linked SOC stocks at 556 old-growth Swiss forest sites from 350 to 2000 m a.s.l. to a comprehensive set of environmental variables, encompassing climate (mean annual precipitation, MAP: 700–2100 mm, mean annual temperature, MAT: 0–12 °C), soil properties, and forest types. In addition, we compared measured SOC stocks with stocks simulated by the Yasso20 model, which is widely used for reporting SOC stock changes. Since Yasso20 is driven solely by litter inputs and climate, deviations between modeled and measured stocks can reveal the significance of additional factors such as organo-mineral interactions that we hypothesized to be crucial for SOC stocks.